Revisiting Indonesian Legal Framework for Juvenile Justice: Ensuring Procedural Rights for Assault Offenders - Alhakim, Abdurrakhman; Febriyani, Emiliya; Tan, Winsherly; Hutauruk, Rufinus Hotmaulana (UNISSULA, 2024)
Assault crimes are violent by nature and are often perceived as a serious threat to public safety. However, the complexity of each crime needs to be analyzed thoroughly in a legal procedure to make sure that important values and principles are applied. This is particularly important among juvenile offenders, where the enforcement of justice needs to be upheld without sacrificing the future of youth. This research is done to analyze the challenges in ensuring procedural rights for juvenile assault offenders in Indonesia. Through the normative legal research method combined with a statutory approach, this research uncovers the legal challenges that juveniles face in accessing their procedural rights in Indonesia’s juvenile justice system and how these challenges can be improved. Analysis of this research finds that the Indonesian legal framework is still lacking in many ways, particularly in ensuring the right to ease of access to information regarding the case and the protection of privacy. The analysisThe analysis also shows that these issues cause conflicts with other laws, constitutional principles, and international standards. This research not only highlights the gaps in Indonesia’s juvenile justice system but also lays a theoretical foundation for developing a more holistic and rights-based approach to juvenile justice reform.